Reducing Hospital Length of Stay for Total Joint Arthroplasty Patients: Effects of Extended Physical Therapy Staffing and Day of Surgery Evaluations. Issue 3 (July 2020) - Phillips, Elizabeth A.; Dalton, Jennifer R.; Childress, Ryan E.; Heidel, Robert E.
Abstract : Purpose: The Rehabilitation Department at the University of Tennessee Medical Center in Knoxville, Tennessee, changed its staffing model in an effort to increase efficiency and reduce hospital length of stay (LOS) without compromising safety for patients undergoing total joint arthroplasty (TJA). This study was designed to reveal effects of extended physical therapy (PT) coverage on TJA patient safety and LOS at our hospital. Methods: Our study is a retrospective chart review including 775 patients. After a staffing change involving the addition of an evening PT shift, we gathered data on patients with TJA in 2 groups: (1) before staffing change and (2) after staffing change. We examined the percentage of patients in each group who received a day of surgery (DOS) PT evaluation and tracked each group's incidence of adverse events and hospital LOS. We then compared outcomes between groups. Results: The percentage of Patients who received a DOS PT evaluation increased from 64.5% prestaffing change to 97.0% poststaffing change. Hospital LOS decreased from 2.30 days (SD = 0.9) in the prestaffing change group to 2.16 days (SD = 0.8) in the poststaffing change group, with no difference in incidence of adverse events between groups. The frequency of adverse events tracked in this study was only 6.6% in each group, indicating that the greater frequency of DOS PT evaluations did not increase the incidence of adverse events or compromise patients' safety. Conclusions: A staffing change involving extended PT evening coverage resulted in a higher percentage of patients with TJA receiving a DOS PT evaluation, no increase of adverse events, and a statistically significant decrease in hospital LOS.